DIMENSI EKONOMI POLITIK PEMBERDAYAAN EKONOMI RAKYAT - Didin S. Damanhuri (Journal of Indonesian Economy and Business (JIEB), 2000)
This article develops arguments proposing people centered development as a way for Indonesia to emerge from the crisis into more prosperous country. The discussion centered around the theoretical perspective and historical-structural of the people centered development. The article then discusses the people centered economy within the multi-parties systems. The paper concludes that resource based industrialization, a major strategy of Indonesia to emerge from the crisis.